Approaches for creating sustainable biomass production in a reclaimed fen in the Alberta Oil Sands Region, Canada - Messner, Lewis Erwin, author; Cooper, David J., advisor; Paschke, Mark, committee member; Brown, Cynthia, committee member (Colorado State University. Libraries, 2019)
Oil sands surface mining in the boreal region of Alberta, Canada alters the natural hydrologic processes, vegetation, and geochemistry of affected ecosystems. Peat accumulating bogs and fens cover approximately 30% of the oil sands region and function as long-term carbon sinks. The government of Alberta has legislated that disturbed areas be reclaimed to "equivalent land capacity." However, no guidelines exist for reclaiming peatlands in post-mined landscapes. A pilot fen was constructed on Suncor's Millennium oil sands mine in 2013 and I analyzed the effects on annual biomass growth by introducing plants as seeds, seedlings, and rhizome fragments from locally harvested material. Total above-ground biomass (AGB) in year five was 460 ± 30.7 g m-2 (n 56) and was comparable to natural fens in the region. Total living below-ground biomass (BGB) averaged 1640 ± 99.9 g m-2 (n 56) by year five, falling slightly below ranges for regional fens. When averaged across all treatments, C. aquatilis produced the greatest AGB (404 ± 32.8 g m-2, n 56) in year five and represented over 70% (se 1.520) of the site total biomass. AGB of C. aquatilis and J. balticus and total AGB and BGB were positively correlated with water table depth. Total BGB was positively correlated with electrical conductivity. Typha latifolia AGB was significantly affected by removal treatments when averaged across sampling years. Plant derived carbon inputs to reclaimed peatlands and long-term storage are characterized in part by the effects of abiotic variables on vascular plant biomass. Results from this study provide guidance for evaluating reclaimed post-mined fens in Alberta, Canada.
Keywords: annual growth; oil sands; reclamation; fen; Alberta; peatlands